Styrene maleic acid micelles as a nanocarrier system for oral anticancer drug delivery – dual uptake through enterocytes and M-cells - Parayath, Neha N (Int J Nanomedicine, 2015)
Drug delivery systems could potentially overcome low bioavailability and gastrointestinal toxicity, which are the major challenges for the development of oral anticancer drugs. Herein, we demonstrate the ability of styrene maleic acid (SMA) nanomicelles encapsulating epirubicin to traverse in vitro and ex vivo models of the intestinal epithelium without affecting the tissue integrity. Further, SMA micelles encapsulating a fluorescent dye dioctadecyl-3,3,3′,3′-tetramethylindocarbocyanine perchlorate (DiI) showed twofold higher accumulation in the liver and spleen, 15-fold higher accumulation in the tumor, and sixfold higher accumulation in the lung as compared with the free DiI, following oral administration in a mice xenograft breast cancer model. Additionally, SMA micelles showed colocalization with microfold (M)-cells and accumulation in Peyer’s patches, which together confirms the M-cell mediated uptake and transport of SMA micelles. Our results indicate that SMA micelles, showing dual uptake by enterocytes and M-cells, are a potential tool for safe oral anticancer drug delivery.